Guerilla Pedagogy: Revaluating Knowledge Mobilization in Research-Creation and Sustaining Art in Conflict Zones (Imaginations: Journal of Cross-Cultural Image Studies, 2025)
This article focusses on the exploration of avenues of dissemination within research-creation methodology – and whether the pedagogical boundaries that research-creation attempts at dismantling within research and practice (especially with respect to film and media) are sustained when the project reaches the dissemination stage. Much like guerilla warfare, where smaller bands of rebels and fighters attack and take on an enemy seemingly much bigger in power than themselves, I view guerilla pedagogy as a methodology of teaching, creating, and disseminating knowledge and art that challenges the confines of corporatized neoliberal universities and hypocritical geopolitical processes which restrict the flow of knowledge in spaces of conflict zones, and fundamentally subverts pre-conceived ideas of the roles of the pedagogue and the student. Through understanding the critical nature of research-creation in decolonizing the production of knowledge, this article explores the necessity of decolonizing prevailing methods of knowledge mobilization. To that end, we try to understand what decolonized knowledge mobilization could look like within research-creation and as research-creation itself. This evaluation happens through studying guerilla pedagogy both as a way of knowledge production in research as well as a method of knowledge mobilization within research-creation. This is done through the extensive academic work conducted on guerilla techniques in different aspects of academia, pedagogy, and activism, as well as through an experiential account of my fieldwork in Kashmir. Research-creation has the potential to facilitate the processes of guerilla pedagogy, creatively evolving it for different political and epistemological circumstances – catering it to the audience and students who require it the most in the way they need it the most. As Weems mentions, “our task is to engage the world’s subaltern in places where they speak, unheard.”